Produção recombinante, caracterização enzimática e estudos sobre a ocorrência de pectinases no "bicudo da cana-de-açúcar" (Sphenophorus levis, Curculionidae) - Evangelista, Danilo Elton (2012)
Plant cell wall confers to the cell plant, structural support as well as protection against pathogens and phytophagous. Among the cell wall polysaccharides includes pectic substances, which are composed of partially methyl-esterified galacturonic acid residues linked by α-1,4 glycosidic bonds. These enzymes are often synthesized by phytophatogenic micro-organisms for invasion of host plant or by own plant for modeling plant cell wall. The pectic substances are the major component of middle lamella and are natural degraded by pectinases action. Pectin methylesterase (PME) catalysis removes methyl-ester groups, and the Endo-polygalacturonase (Endo-PG) promoves the randomly hydrolysis reaction of α-1,4 bonds. One of the most importante agricultural pest species of the family Curculionidae (Coleoptera: Curculionidae) is Sphenophorus levis, the sugarcane weevil. The larvae of this insect penetrate into the rhizome and build galleries in the stem, decreasing productivity and causing the death of the plant. Large damages to the crop like that are significant in the costs of products derived from sugarcane. Considering the impact of this pest in the sugarcane crop and the absence of efficient method for control, new strategies for controlling are still necessary. The analysis of the cDNA library of S. levis larvaes shows the presence of one PME and one Endo-PG genes that we called Sl-PME and Sl-EndoPG respectively. Considering the importance of studies of insect pests and the extensively use of theses pectinases in different industry fields, we performed the characterization of genomic sequences coding for S. levis pectinases (Sl-Pectinases). It was also carried out the production and characterization of a Sl-PME and a Sl-EndoPG recombinant, expressed in heterologous system. We also accomplished analysis of gene expression by qRTPCR in different stages of development as well as different tissues, and phylogenetic studies between Sl-Pectinases and other pectinases from different kingdoms. The Sl- Pectinases sequences identified, show more similar to homologous insect genes deposited in the GenBank, especially with Sitophilus oryzae. The phylogenetic analysis indicates that the insect group is more correlated with bacteria group and fungi group respectively to PMEs and EndoPGs sequences. Pectinases genomic sequences revealed two introns for Sl-EndoPG gene with 53 and 166 bp, but no one for Sl-PME gene. Both of Sl-Pectinases Recombinant showed catalytic activity. The recombinant Sl-EndoPG shows optimal activity at pH 5,06 ± 0,27 and 49,74 ± 2,49 oC, but extremely low thermostability. For the polygalacturonic acid no-methylated as substract, the enzyme revealed Km = 3,88 mg.mL-1, Vmax = 21.96 μM.s-1 e Kcat = 3.137 s-1; for the citrus pectin partially methylated as substract, the enzyme presented Km = 4,98 mg.mL-1, Vmax = 17,19 μM.s-1 e Kcat = 2.456 s-1. Results in expression analysis suggest that S. levis pectinases have a digestive enzymes role, actting on the midgut. The present work represents the first pectinases of insect produced in Pichia pastoris heterologous system and characterized as optimal conditions of activity, thermostability and kinetic parameters.